STUDY OF GASEOUS FLOW AND THE INFLUENCE OF PRIMARY AIR AND SWIRL BURNER DISTANCE ON TEMPERATURE PROFILE IN ROTARY KILN USING COMPUTATIONAL FLUID DYNAMIC (CFD) - Satriya Pinandhita, Arjuna
Rotary kilns are tools which wide range used and mostly are used in cement production process. Key parameter of rotary kiln is temperature profile inside rotary kiln. The products quality and efficiency of rotary kilns can be improved if the temperature could be set precisely and heat distribution inside rotary kiln is known. One of the ways can be done to find out temperature profile in rotary kiln by using Computational Fluid Dynamics (CFD) simulation. Several operating parameters that affect the work of a rotary kiln including primary air, secondary air, burner distance, etc. In this research, a CFD simulation was performed on rotary kiln to see a heat flow and the influence of primary air and swirl burner distance on temperature profile in rotary kiln. The simulation begins from making a geometry based on literature using Autodesk Inventor. Then, the geometry is meshed before simulated using Ansys Fluent. The simulation was set-up with activated energy, realizable k-? standard wall, and nonpremixed combustion models with CH4 for the fuel. Then, the simulations was performed using SIMPLE methods with calculation close to convergent. From these simulations, it was found that the form of flow was a turbulent at burner outlet which caused by the existance of swirl in the burner. For primary air with temperature 353 K, 523 K, and 773 K generate flame temperature consecutively 1802 K, 1939 K, and 2197 K which increase temperature profil in rotary kiln. For swirl burner with distance 0 m; 2,5 m; 5 m; dan 10 m, temperature at 29 m center point from burner outlet and gas outlet consecutively 1740 K and 1520 K; 1700 and 1510 K; 1660 K and 1500K; 1620 K and 1495 K.